Strength and water permeability of concrete containing coal bottom ash as cement and fine aggregate replacement material - Basirun, Nurul Fasihah (2019)
The reuse of industrial waste as a substitute of concrete ingredents presents an alternative solution for minimizing waste and producing sustainable concrete construction. However, coal bottom ash (CBA) is the one of the major waste product, generated by coal operated thermal powerplants. Therefore, study aims to utilization of grinded coal bottom ash (GCBA) and ungrinded coal bottom ash (UGCBA) as a cement and fine aggregate replacement material in concrete and evaluate its strength and durability performance. In this study, GCBA was grinded for 20, 30 and 40 hours to produce fine particles as comparable to cement. Initially, particle size distribution (PSD) analysis and X-ray Fluorescence (XRF) analysis were carried out to evaluate the particles characteristics before and after grinding .The 20% GCBA produced through 30 hour grinding period was considered as optimum percentage based on 28 day compressive strength. Then, the concrete specimens were incorporated 20% GCBA as cement replacement and varying proportion of fine aggregate were replaced with UGCBA at 5%, 10%, 15% and 20% by weight of fine aggregate. Afterward, compressive strength and water permeability tests were evaluated at 7, 28, 56, 90 and 180 days respectively. It was observed that concrete containing GCBA and UGCBA for all percentage replacement were found to be higher compressive strength and water permeability coefficient as compared to the control concrete. However, it was noticed that lower compressive strength and higher value of water permeability coefficient compared to control samples after 90 days up to 180 days. Besides that, at the age of 180 days it was also observed that concrete containing more than 20% replacement of fine aggregate gives the lower compressive strength as compared to control mix concrete. Hence, it can be concluded that 20% replacement of cement with GCBA was found to be effective for improvement of compressive strength and reduction in water permeability. This study declared that compressive strength decreases and water permeability increases when optimum GCBA incorporated with UGCBA in concrete.